PERAN HUMAS PEMERINTAH KABUPATEN SRAGEN DALAM PENGELOLAAN ISI INFORMASI WEBSITE PEMDA SEBAGAI MEDIA COMMUNICATIONS RELATIONS DENGAN MASYARAKAT - Meilyna Diah Anggrahini; Christina Rochayanti; Edwi Arief Sosiawan (Jurnal Ilmu Komunikasi, 2008)
Human relation is an integral part of an organization or company since all of activities conducted is intented to create organizations or companys positive image before the public. For creating such positive image to the existing role of human relations in the management of infor- mational contens of regional government’s website as media of communications relation with society. Human relations has role as communication fasilitatos i.e legal practisioner behaving as communicator or mediator to create two why or reciprocal communication between the organization or company and its public though online media. The purpose of this reseach was to know the role of human relations of regional Government of Sragen Regency in management of informational content in Regional Government’s website as communications relations with society in Regional Government of Sragen Regency. This reseach used descriptive qualitative reseach method. Technique of data collection was conducted by interview, observation and literal study. The result of this research suggests that human relation of Regional Government of Sragen Regency has role in organisational management in management process of informational contents contained in Regional Government’s website. Human relations strives to fulfill social demand to gain information on all policies, program and activated conducted by government. However, active participations of society is still felt as lack. Communication relations relate between government and society through online media has not been conducted optimally. There is still few amount of society that knows Regional Government’s website. Society only takes the advantages of website merely for gaining information. Thus, human relation keeps maintaining the use of conservative media as medium for conveying information to the cociety.